2022
DOI: 10.3389/fmicb.2022.947102
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of lactoferrin: A bibliometric analysis from 2000 to early 2022

Abstract: BackgroundHere, a bibliometric and knowledge map analysis are used to analyze the research hot spots and development trends regarding the antibacterial effect of lactoferrin (LF). By looking for research hot spots and new topics, we provide new clues and research directions for future research.MethodsArticles and reviews regarding the antibacterial effect of LF were retrieved and from the Web of Science Core Collection (WoSCC) on 25 June 2022. CiteSpace and VOSviewer were used to conduct the bibliometric and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
(47 reference statements)
0
6
0
1
Order By: Relevance
“…According to a study by Beshay M. et al, the presence of contusion was found to be associated with mortality (9).…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Beshay M. et al, the presence of contusion was found to be associated with mortality (9).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previously performed studies demonstrate the use of different types of substances, mostly from the range of biomaterials (e.g., hydroxyapatite crystals, nanostructures) that are functionalized with Lf and with promising results in tissue engineering [ 38 , 61 ]. The antimicrobial properties of Lf are the most studied [ 36 , 61 , 62 , 63 ]. Several mechanisms are involved in this activity, such as iron chelation, thus depriving microorganisms of this nutrient, or direct interaction with bacterial surface components [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would even seem that LF could stimulate the proliferation of probiotic bacteria [ 63 ]. The exploration of the LF peptide mechanisms of action for the antibacterial effects mainly revealed (i) the sequestration of bacteria and their deprivation in iron (essential for their survival) by LF given its iron-binding ability [ 64 ]; (ii) the potential of LF in interacting with LPS of gram-negative bacteria, thus considerably hampering their growth [ 8 , 65 , 66 ]; (iii) the LF competency of binding with receptors on microorganisms to obstruct the transport of nutrients, thereby restraining bacterial synthesis and metabolism [ 67 , 68 ]; (iv) the inhibition of microbial enzyme activity by LF [ 67 ]; (v) the LF-mediated prevention of biofilm formation by bacteria [ 69 ]; (vi) the capacity of LF to release antibacterial peptide lactoferricin and other bioactive peptides following hydrolysis by pepsin [ 70 , 71 , 72 ]; and (vii) the direct antimicrobial activities exerted by LF [ 73 ]. It should be noted that the impact of LF is not limited to bacteria, but can also extend to antivirals [ 74 , 75 , 76 ], antiprotozoal [ 77 ], and antifungal [ 78 ] activities.…”
Section: General Lactoferrin Propertiesmentioning
confidence: 99%